High frequency noise modeling in low inversion region - Chan, Kelvin Lye Hock (2015)
The design of the low-voltage low-power RF circuit has become increasingly grown in demand. The existence of noise in MOSFET is one of the main challenges of the low-voltage low-power RFIC design. The performance of RF circuits strongly relies on upon how accurate the high frequency noise characteristics of the transistors are modeled and predicted. Therefore, it is necessary to have accurate noise models of MOSFETs, which are continuous from weak to strong inversion. For MOSFETs under sub-threshold condition, a new high frequency drain current noise model is developed to include a new component of noise called junction noise, which is the additional drain current noise due to the high-frequency shot noise in the source-bulk and drain-bulk junctions. The proposed model features to capture the unique characteristic of the sub-threshold drain current noise spectral density that is gate bias independent and frequency dependent. A simple model formulation is proposed together with its parameter extraction technique, which utilizes Y-parameter analysis on the RF small-signal equivalent circuit. Besides the drain current noise, new models are derived for induced gate noise and its cross-correlation with channel thermal noise, under weak-inversion operation. Unified models, which are analytical and threshold-voltage based, are developed for short-channel MOSFETs to predict the characteristics of the drain current noise, the gate current noise as well as their cross-correlation. The models are valid for all regions of operation and exhibit excellent continuity with smooth transition. New smoothening functions are developed and are validated to converge with the piece-wise models derived for each of the weak and the strong inversion regions.The proposed models for the drain current noise, the gate current noise and their cross-correlation as well as the four noise parameters are verified with measurement data. The results manifest that the accuracy of noise parameters in the sub-threshold region is significantly improved when the noise due to the junctions is accounted in the drain current noise modeling.